The impacts of the Yogunagac-Karakocan ve Dedebeg-Mazgirt thermal and mineral waters on the Peri Stream Water - Oztekin-Okan, Ozlem; Kalender, Leyla; Cetindag, Bahattin (Pamukkale Univ, 2019)
In this study, the effects of the thermal and mineral waters in Yogunagac-Karakocan and Dedebeg-Mazgirt on the surface waters along the direction of the Peri Stream were determined that the samples were taken in two different periods (May/September). The distributions of the studied ions and some complex ions at the mixture setting Peri Stream and thermal and mineral waters are shown to decrease of K, Al, Cu, Mn and increase of Cl, Mg, HCO3, Ca, Na, SO4, As, B, Ba, Fe, Sb and Sr in May, while increasing of Cl, Mg, HCO3, Ca, Na, B, Mn, Al and Sb, decreasing SO4, K, Pb, Fe and Sr in the Peri stream water in September. While increasing of ion diversity due to rain fall during in May. According to the calculated saturation indices, Peri, Ohi streams and thermal and mineralized waters are oversaturated with minerals containing Fe, such as goethite and hematite. High Fe concentrations in stream and thermal and mineral waters should be related to the dissolution of Fe-bearing minerals in volcanites, sedimentary rocks and metamorphites. Oversaturation of the waters with clay minerals such as illite and kaolinite is related with the dissolution of clay minerals occurred in fractures and faults related with the active tectonism in the study area. The Peri Stream water sample when mixed with thermal and mineral waters, is classified as low quality water in terms of its contents of Ca, Mg, Na, K, Cl, SO4, HCO3, Al, Co, Mn, P and Pb when assessed according to the averages of intra-continental water resources.
Keywords: Peri stream; Thermal water; Geochemistry